2016
DOI: 10.1159/000443958
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Hypothyroidism: Long-Term Experience with Early and High Levothyroxine Dosage

Abstract: Aim: To assess the management and outcome of the congenital hypothyroidism (CH) patients followed at our institution since the introduction of systemic neonatal screening for CH. Study Design: The records of 139 CH patients referred to our center between 1978 and 2014 were retrospectively reviewed. Biochemical and imaging data at diagnosis, initial treatment and growth were analyzed. Results: 111 patients had thyroid dysgenesis (64 ectopy, 46 athyreosis and 1 hypoplasia) and 28 patients had a gland in situ (17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
1
13
0
1
Order By: Relevance
“…CH is a systemic metabolic disorder due to insufficient production of thyroid hormones due to thyroid gland malformation or disturbance in hormonal biosynthesis. It is a hereditary disease that, if left untreated, seriously compromises intellectual growth and development, since it is considered one of the few causes of intellectual disability that can be prevented when diagnosed and treated early 5,8 . PKU refers to the autosomal recessive metabolic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…CH is a systemic metabolic disorder due to insufficient production of thyroid hormones due to thyroid gland malformation or disturbance in hormonal biosynthesis. It is a hereditary disease that, if left untreated, seriously compromises intellectual growth and development, since it is considered one of the few causes of intellectual disability that can be prevented when diagnosed and treated early 5,8 . PKU refers to the autosomal recessive metabolic disorder.…”
Section: Introductionmentioning
confidence: 99%
“…This was attributed to the fact that the majority of patients were from rural areas and probably have some difficulties in accessing their results of screening as well as in admission to our tertiary pediatric endocrine centre. While in some studies, a female predominance has been reported, some others, showed a male predominance ( 8 , 9 , 10 , 11 , 12 , 13 , 14 ). In the present study, there was a slight female predominance.…”
Section: Discussionmentioning
confidence: 92%
“…Patients with eutopic thyroid gland account for (54%) of cases with permanent CH ( Figure 1 ). When considering the aetiology of permanent CH, in previous studies, thyroid dysgenesis was reported to cause 75-85% of permanent CH cases which was followed by dyshormonogenesis cases with eutopic glands ( 5 , 13 ). However, a considerable shift has been observed in the incidence rate as well as the ratio of transient and permanent cases with a change in the cut-off values which had been used for neonatal screening programs ( 5 , 8 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early and continuous treatment with LT4 has been shown to promote normal growth [8,9] and BMD or other indices of bone health [10][11][12] in children with congenital hypothyroidism, relative to their euthyroid peers ( Fig. 1), and normal BMD in adults [13].…”
Section: Patients With Congenital Hypothyroidismmentioning
confidence: 99%